Assessing the Effectiveness and Feasibility of a Clinical Supervision Course Learning Module - Samsilayurni Samsilayurni; Erwan Dirgantara (STAI Hubbulwathan Duri, 2025)
This study aims to develop an innovative learning module for Clinical Supervision courses that aligns with contemporary practices in educational supervision. The module is designed to support both effective learning and the application of modern pedagogical approaches. The research employed a Research and Development (RD) approach using the 4D model—Define, Design, Develop, and Disseminate. Module content and media were validated by two subject matter experts and two media design experts. A limited trial was conducted with seventh-semester students from the Educational Administration program. Validation results indicated high feasibility: 87.05% from subject matter experts and 83.33% from media experts, both falling into the